2008
DOI: 10.1111/j.1467-8624.2008.01147.x
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Between Child Behavior Patterns and Parent Supervision: Implications for Children’s Risk of Unintentional Injury

Abstract: Unintentional injuries are the leading cause of death for children. Prior research has implicated both child behavioral attributes and parent supervisory patterns as risk factors. The present study assessed interactions between these two risk factors and determined whether supervision moderates the relation between child attributes and injury. Mothers completed questionnaire measures of child attributes and supervisory patterns and also recorded how they supervised their young child (2-5 years) at home on each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(61 citation statements)
references
References 59 publications
4
52
0
2
Order By: Relevance
“…Recent research findings confirm that risk factors for injury to young children include not only child behavioral attributes but also caregiver supervisory patterns [29]. Increasing parental awareness of the injury-risk implications of young children's emerging advancements in motor skills is essential to aid their making appropriate decisions about children's supervisory needs.…”
Section: Discussionmentioning
confidence: 95%
“…Recent research findings confirm that risk factors for injury to young children include not only child behavioral attributes but also caregiver supervisory patterns [29]. Increasing parental awareness of the injury-risk implications of young children's emerging advancements in motor skills is essential to aid their making appropriate decisions about children's supervisory needs.…”
Section: Discussionmentioning
confidence: 95%
“…6 However, there is contradictory evidence to indicate whether parental home safety education is effective in actual home safety behaviors and the decrease in the risk of injuries. In a previous study, the intervention group receiving a home safety education demonstrated a significantly higher average overall safety score at followup with telephone interviewing than the control group in a previous study.…”
Section: Discussionmentioning
confidence: 99%
“…Due to their increased susceptibilities, children are highly dependent on adult provision of a safe environment and protection from contact with hazards (5). Further, parental attitudes and behaviors are an important consideration in designing successful injury interventions (6). Therefore, prevention efforts directed to parents such as interactive education programs, home-based parent education programs, and the provision of safety devices free of charge or at reduced cost or the combination of these interventions have been conducted in recent years with the aim of the improvements of parental home safety behaviors (7)(8)(9).…”
Section: Anahtar Sözcükler: Ev Kazaları Korunmamentioning
confidence: 99%
“…The individual level Causes of injury on the individual level primarily include the child's attributes and the interaction with the agent and the environment. The child's developmental stage and attributes, such as clinical disorders, temperament traits and aspects of cognitive functioning, are major factors contributing to the odds of a specific injury occurring (Morrongiello, Klemencic, & Corbett, 2008). However, there is no evidence or reason to believe that Arab and Jewish children differ in their developmental characteristics or rates of temperament traits that would contribute to a difference in injury rate.…”
Section: Unintentional Injuries Among Arab and Jewish Children In Israelmentioning
confidence: 98%